High-performance An/Ti/Ge/Pd ohmic contacts on n-Type In0.5Ga0.5P - Chai, CY; Wu, JW; Guo, JD; Huang, JA; Lai, YL; Chan, SH; Chang, CY; Chan, YJ; Cheng, HC (My University, 1996)
High-performance Au/Ti/Ge/Pd ohmic contacts on n(+)-In0.5Ga0.5P have been fabricated for the first time. Using an n(+)-In0.5Ga0.5P epitaxial layer grown by low pressure metalorganic chemical vapor deposition (LP-MOCVD) with a Si dopant concentration of about 2 x 10(18) cm(-3), the minimum specific contact resistivity is as low as 1.2 x 10(-5) Ohm . cm(2), which is much lower than that of AuGeNi contacts after rapid thermal annealing at 400 degrees C for 60 s. The thermal stability of the Au/Ti/Ge/Pd system is significantly higher than that of conventional AuGeNi due to the introduction of the Ti barrier layer. Many holes and islands are observed on the surfaces of samples annealed at high temperature. The outdiffusion of P from the decomposed In0.5Ga0.5P substrate and agglomeration of Pd and Ge are the primary causes of contact degradation.
Keywords: Au/Ti/Ge/Pd; ohmic contact; n-type In0.5Ga0.5P; LP-MOCVD